2016
DOI: 10.1007/s10549-016-3737-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of breast cancer incidence in patients of lymphangioleiomyomatosis

Abstract: Molecular evidence has linked the pathophysiology of lymphangioleiomyomatosis (LAM) to that of metastatic breast cancer. Following on this observation, we assessed the association between LAM and subsequent breast cancer. An epidemiological study was carried out using three LAM country cohorts, from Japan, Spain, and the United Kingdom. The number of incident breast cancer cases observed in these cohorts was compared with the number expected on the basis of the country-specific incidence rates for the period 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Estrogens have been shown to boost the metastatic potential in a LAM cell model (21), and progesterone and estradiol synergistically interact in this process (22). The similarities between LAM and cancer might extend to shared disease susceptibility (23,24)…”
Section: Introductionmentioning
confidence: 99%
“…Estrogens have been shown to boost the metastatic potential in a LAM cell model (21), and progesterone and estradiol synergistically interact in this process (22). The similarities between LAM and cancer might extend to shared disease susceptibility (23,24)…”
Section: Introductionmentioning
confidence: 99%
“…1,47,48 A hitherto the largest epidemiological study indicated that sporadic LAM patients were at a higher risk of developing invasive BC relative to those from the general population. 49 Recent study supported that high levels of serum CA-125 (an OC biomarker) were associated with disease progression of LAM. 50 Due to the low yield of the report of LAM disease linked with estrogen-dependent disease, such as BC or OC, misregulation of these genes are prospective research fields to elucidate novel pathogenesis of LAM in the future.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, isolated LAM cells from the lungs exhibit positive immunoreactivity for ER and PR . A hitherto the largest epidemiological study indicated that sporadic LAM patients were at a higher risk of developing invasive BC relative to those from the general population . Recent study supported that high levels of serum CA‐125 (an OC biomarker) were associated with disease progression of LAM .…”
Section: Discussionmentioning
confidence: 99%
“…There have been few previously reported cases or studies on the incidence of breast cancer in patients with lymphangioleiomyomatosis (LAM). In 2016, Nunez et al analyzed the incidence of three patient cohorts with LAM from three different countries and identified an increased risk of breast cancer in these patient populations [6]. The patient in this case report had a previous diagnosis of angiomyolipoma 19 years previously, but the relevance of this is unclear.…”
Section: Discussionmentioning
confidence: 95%